Diversity of Sargassum spp on Lendang Luar Beach, West Nusa Tenggara - Ghazali, Mursal; Saraswati, Putu Bella Aprillia; Sukiman, Sukiman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Sargassum is the most diverse genus in the brown algae Fucales and represents key ecologically important processes in marine ecosystems. There are 150 species found in tropical, subtropical and boreal waters. This study aims to know the biodiversity of the Sargassum genus in Lendang Luar Beach, West Nusa Tenggara. The study results will give knowledge about the different species of Sargassum based on their different morphologies and anatomical structures. The research method is divided into three work stages, which are collected on the location site, observing forms and observing anatomy. It collects algae by random sampling and serving cauloid, filoid, Vesicle (float) and receptacle (organs of breeding). Anatomical observation of the cortex and pith parts of stalk and thallus of Sargassum. According to the observation, four species of Sargassum were found at Rendang Luar Beach, North Lombok, West Nusa Tenggara: Sargassum crassifolium, Sargassum cristaefolium, Sargassum echinocarpum, and Sargassum polycistum. Such a result is that the variation in morphology is supported by the variation in anatomy.